PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. AEM - Afipuddien, Afipuddien; Sugiyono, Sugiyono (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2018)
The aim of this study was to analyze the influences of Perceived Organizational Support, Affective Commitment and Organizational Citizenship Behavior regarding to the Employee Performance which conducted in PT. Nur Medinah Intermedia, thereby providing benefits in academic literature and provide information prior to the making decisions. By using primary data which colleted by distributing questionnaires to 86 respondences and through field research as well. The study was conducted by analyzing through correlation and regression. Results of hypothesis testing indicated that; There was positive and significant influences between Perceived Organizational Support to the Affective Commitment. There isÂ  a positive and significant impact with a high degree of influence between Perceived Organizational Support to the Organizational Citizenship Behavior. There is a positive and significant between Affective Commitment and Organizational Citizenship Behavior. There is a positive and significant influences between Employee Performance to the Perceived Organizational Support. There is a positive and significant influences between the Employee Performance to the Affevtive Commitment. There is positive and significant correlation between Organizational Citizenship Behavior to the Employee Performance.